2015
DOI: 10.1038/srep12420
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly carbon-nanodot-based fluorescent paints for advanced photocatalytic systems

Abstract: Fluorescent carbon nanomaterials, especially zero-dimensional (0D) carbon nanodots (CDs), are widely used in broad biological and optoelectronic applications. CDs have unique characteristics such as strong fluorescence, biocompatibility, sun-light response, and capability of mass-production. Beyond the previous green CD obtained from harmful natural substances, we report a new type of fluid-based fluorescent CD paints (C-paints) derived from polyethylene glycol (PEG; via simple ultrasound irradiation at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…At the purification degree of 90%, the cell viability remained high: over 86% for HeLa cells, 92% for MCF-7 cells, and 90% for HaCaT cells. We found that the water purified (to degrees up to 90%) by the H-TiO 2 120 photocatalyst left non- or minimal cytotoxicity in the cells 51 . This result confirms that the water purified by the H-TiO 2 120 photocatalysts is safe for humans.…”
Section: Resultsmentioning
confidence: 83%
“…At the purification degree of 90%, the cell viability remained high: over 86% for HeLa cells, 92% for MCF-7 cells, and 90% for HaCaT cells. We found that the water purified (to degrees up to 90%) by the H-TiO 2 120 photocatalyst left non- or minimal cytotoxicity in the cells 51 . This result confirms that the water purified by the H-TiO 2 120 photocatalysts is safe for humans.…”
Section: Resultsmentioning
confidence: 83%
“…The most commonly used bottom-up approaches to produce CDs include microwave approach [31,32,33,34], thermal decomposition [35,36], ultrasonic treatment [37,38], and hydrothermal treatment [39,40,41,42], among others (e.g., pyrolysis [43]). This route utilizes various small or large precursor materials, including both natural and synthetic polymers.…”
Section: Synthesis Methods Of Carbon Dotsmentioning
confidence: 99%
“…Bare polyethylene glycol (PEG, Mn = 300) was treated with simple ultrasound irradiation at room temperature for 1, 2, 3, or 4 h without additional solvents, achieving CDs with size of 2-6 nm and quantum yield of up to 14% [37]. The PL emission intensity gradually increased with the increasing synthesis time.…”
Section: Synthesis Methods Of Carbon Dotsmentioning
confidence: 99%
See 2 more Smart Citations